2021
DOI: 10.3390/catal11050556
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Photocatalytic Reactors Design and Operating Parameters on the Wastewater Organic Pollutants Removal—A Mini-Review

Abstract: The organic pollutants removal by conventional methods (adsorption, coagulation, filtration, microorganism and enzymes) showed important limitation due to the reluctance of these molecules. An alternative to this issue is represented by the photocatalytic technology considered as an advanced oxidation process (AOP). The photoreactors design and concepts vary based on the working regime (static or dynamic), photocatalyst morphology (powders or bulk) and volume. This mini-review aims to provide specific guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 107 publications
0
22
0
Order By: Relevance
“…Recent studies by Enesca (2021) reported that using the inappropriate photoreactor design may significantly increase energy consumption, improperly distribute photons, or cause the catalyst to deactivate, all of which have an adverse effect on photocatalytic efficiency. (Enesca 2021).…”
Section: Factors Influencing Photocatalytic Reaction Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies by Enesca (2021) reported that using the inappropriate photoreactor design may significantly increase energy consumption, improperly distribute photons, or cause the catalyst to deactivate, all of which have an adverse effect on photocatalytic efficiency. (Enesca 2021).…”
Section: Factors Influencing Photocatalytic Reaction Processmentioning
confidence: 99%
“…Recent studies by Enesca (2021) reported that using the inappropriate photoreactor design may significantly increase energy consumption, improperly distribute photons, or cause the catalyst to deactivate, all of which have an adverse effect on photocatalytic efficiency. (Enesca 2021). Thus the main obstacle in the development of highly efficient photocatalytic reactors is the establishment of effective reactor designs for intermediate and large-scale use, as demanded for the purpose of industrial or commercial applications (Abhang et al 2011).…”
Section: Factors Influencing Photocatalytic Reaction Processmentioning
confidence: 99%
“…(5) The species inside the monolith are homogeneous and incompressible Newtonian fluid. (6) The photocatalyst coating with the same thickness on the reaction surface consists of 2.6wt% NiO/InTaO 4 (imp). The photocatalytic kinetic model was established according the OFMR experiments with NiO/InTaO 4 as catalysts from Liou et al [36] When the photoreaction took place at the room temperature with Mercury lamps as the light source, methanol was measured as the major product.…”
Section: Modelsmentioning
confidence: 99%
“…Furthermore, the InTaO 4 based photocatalysts show significant potential for photoactivity enhancement by available processes such as the doping process [5]. On the other hand, the photoreactor structure also influences the photocatalytic performance significantly, because it dominates the light transmitting efficiency, molecular diffusion rate, and reaction capacity [6]. Therefore, the design and optimization of photoreactors have attracted a lot of attention [7].…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis has the advantage of completely mineralize organic pollutants more than other conventional treatment methods such as coagulation, flocculation, co-precipitation, and even precipitation that fail to remove highly toxic pollutants even at low concentrations (Enesca, 2021). There are two main groups of advanced oxidation processes for wastewater treatment: homogenous light-induced technology involving the application of ozonation (UV/O 3 and UV/O 3 /H 2 O 2 ) and photo-Fenton processes (UV/Fe 2þ /H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%